Exploration of the hypothalamic-pituitary-adrenal axis in the aged. - Fiszlejder, Leon; Gutiérrez, Sílvia; Valdivieso, Carlos; Leston, Jorge A.; Guitelman, Abraham (Acta Médica Portuguesa, 1980)
In order to investigate the adrenocortical axis in aged people, we have evaluated adrenal function through different dynamic parameters. Seven healthy elderly patients, 4 women and 3 men, whose ages ranged from 70 to 91 years were studied; cortisol concentration in serum was evaluated at 8 a.m. and 4 p.m. (circadian rhythm) as well as the responses to inhibition (Nugent) and stimulation tests (synthetic ACTH and Calcium test). The cortisol levels at 8 a.m. and 4 p.m. were 15 ± 3.5μg/100ml and 7.5± 1.92μg/10Oml respectively. The Nugent test showed a significant inhibition of cortisol (p<0.025); the stimulation tests either with ACTH or Calcium caused a significant increase in circulating cortisol (p<0.005). The results obtained demonstrate both the normality of the basal concentration of cortisol and of the circadian rhythm and the response to the inhibition and stimulation tests. We can draw the conclusion that the aged person has an adequate reserve in the hypothalamic-pituitary-adrenal axis.